Are you what you dress? The association of the male gay self identity to luxury clothes - Altaf, Joyce Gonçalves; Troccoli, Irene Raguenet; Moreira, Mara Bastos (Revista de Administração da UFSM, 2013)
The emergence of the identity of the homosexual modern consumer, favored by the social, economic and psychological conditions produced by capitalism, allowed homosexuals to feel free to express their identity, among other ways through the use of products and services. Thus, understanding what stimulates the consumption of a specific product category by this market niche is no doubt of great importance for the companies that intend to serve this public, considering their attractive consumption profile. This stimulated this exploratory qualitative study, that seeked to identify the relationship between luxury clothing consumption by homosexual men and the development of their extended self, and well as their self image construction. The four steps of the research, done with 12 men, were literature review, in-depth interviews, the filling of two forms (one with Likert scale and the other with a semantic scale), and the analysis of the results. The conclusion is that self concept directly influences the buying behavior of male homosexuals, and that most of the interviewees actually use luxury brands clothes to compose their extended selves.